DEVELOPMENT OF THE LADDER SNAKE GAME MEDIA IN ARABIC LEARNING/ PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA DALAM PEMBELAJARAN BAHASA ARAB - Baroroh, R Umi; Mardliyyah, Aisyam (Ijaz Arabi Journal of Arabic Learning, 2019)
This research was conducted to develop a snake ladder game media for learning Arabic and describes its influence on student learning outcomes, with the subject of class V MI Ma'arif Bego Sleman Yogyakarta. This research belongs to the Research and Development (R D) category. The instruments used in this study were observation, interviews, documentation, material questionnaires, media expert questionnaires, peer reviewer questionnaires, and student responses. The data analysis technique in this study used descriptive analysis in percentage. The results showed that: 1) snakes and ladders playing media for learning Arabic the criteria for "Very Good" percentage was 84.61%, media expert ratings were 91.11%, and peer reviewers were 84.67%. 2) The response of students in the field trial as a whole obtains a "Positive" assessment category with a percentage of 89.58% and the influence of the media on improving student learning outcomes. Based on the results of the analysis, this study shows that the media of snakes and ladders in Arabic learning gets a positive response from students and can be used as one of the media for learning Arabic.Keywords: Development; Instructional Media; Snakes and ladders game.